The origins and development of the English language - Algeo, John; Pyles,Thomas , 1905-1980 (Wadsworth Cengage Learning, 2010)
This text is intended for History of the English Language courses that are generally taken by linguistics and English majors as well as future teachers of English (for whom the course is often required)